THERAPEUTIC ULTRASOUND AS A TREATMENT APPROACH FOR CARPAL TUNNEL SYNDROME - Igor Gawłowski; Paweł Harbut; Dominika Walczak; Weronika Ewa Nowak; Adrian Kruk; Katarzyna Jakubowska; Aleksandra Dorosz; Aleksandra Miśta; Aleksander Białoń; Lidia Jurczenko (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Carpal tunnel syndrome (CTS) is a common compression neuropathy causing pain, paresthesia and impaired hand function. Conservative management includes activity modification, splinting, pharmacotherapy and physical modalities; surgical decompression is indicated for refractory or severe cases. Therapeutic ultrasound (US) is a widely used conservative modality that may exert thermal and non - thermal effects potentially reducing inflammation, promoting tissue repair and improving nerve conduction in CTS.Aim: To review current clinical evidence on the use of therapeutic ultrasound for the management of mild to moderate carpal tunnel syndrome, with emphasis on clinical outcomes, electrophysiological changes, treatment parameters and study quality.Review Methods: A focused literature search of PubMed and Google Scholar was performed using combinations of the following keywords: “therapeutic ultrasound”, “ultrasonography therapy”, “phonophoresis”, “underwater ultrasound”, “carpal tunnel syndrome”, “conservative treatment”, and “randomized trial”. Randomized controlled trials, sham-controlled studies, and comparative clinical studies were prioritized.Conclusion: Therapeutic ultrasound demonstrates potential as a conservative treatment for mild - moderate CTS: several randomized and controlled trials report improvements in pain, symptom severity and certain electrophysiological measures, while other studies show comparable clinical benefit in sham or splint-only groups. Heterogeneity in US dose, mode (continuous vs pulsed), frequency, treatment schedule, concomitant therapies (notably splinting) and short follow - up periods limits firm conclusions. Standardized treatment protocols and larger, well - powered randomized trials with longer follow-up are needed to define optimal parameters and to clarify whether therapeutic ultrasound confers clinically meaningful benefits beyond placebo or standard conservative care.